Faktor-faktor yang mempengaruhi pemanfaatan posyandu lansia di Puskesmas Geulumpang Tiga, Pidie - Zulaikha Zulaikha; Ampera Miko (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Health services at the posyandu for the elderly include examining activities of daily living, weighing, measuring height, measuring blood pressure, health education, and simple laboratory examinations. The level of activity of the elderly in participating in Integrated Healthcare Center (IHC) activities or utilization is still low at 63%. Causative factors are various physical conditions that occur in the elderly, such as being sick, support from family members, the role of health workers and the absence of family members who deliver.Objectives: This study aims to determine the factors that influence the use of IHC for elderly people at the Geulumpang Tiga Public Health Center, Pidie District.Methods: This research was used a descriptive analytic approach, with a cross-sectional design. The method of taking was by standard random sampling with a number of 80 elderly spread across 14 villages. Data were collected by interview and observation. Data collection includes data on the identity of the elderly, data on family support, the role of health workers, the role of cadres and the utilization of the elderly of IHC. Statistical analysis using the Chi-square test with 95% CI.Results: The results showed that the active of IHC for the elderly was 57.7%, the role of the elderly was 60.2%, family support was 60.2% and the role of health workers was 61.4%. Statistically, it also shows that there is a significant relationship between the role of the elderly (p= 0.000), family support (p= 0.004), the role of cadres (p= 0.001) and the role of health workers (p= 0.000) with the utilization of the elderly of IHC in Geulumpang Tiga, Pidie.Conclusion: The factors related to the utilization of the IHC for the elderly are the role of the elderly, family support, the role of cadres and health workers. Suggestions, to health workers and cadres to be able to provide continuous counseling related to elderly of IHC.